Strengthening Networks for Urban Development, Creative Arts, and Tourism in the Lanna Region - Sanvong, Phramaha Kraisorn; Kongtan, Phramaha Attaphon; Somcharoen, Pha Naruepan; Lueangphithak, Pinpinat (Local Administration Journal, 2021)
The objective of this research was to study the network potential, to develop network performance and processes, and to develop innovation, network strengthening, urban development, creative arts, and tourism in Lanna Region (Northern Thailand). This research used qualitative research methodology and action research methodology. The research instruments include structured and non-structured interviews, focus groups, and academic seminars. The research investigated the potential and roles of networks that are involved in developing creative arts and tourism in the Lanna Region. Most of them have roles according to their potential and abilities, such as government sectors, organizations, communities, artists, etc. They perform their own roles and cooperate with each other with linking and coordinating the roles between the networks. The analysis of network potential found that the main strengths were the roles of each network, which were vigorous and can be developed together. The weakness is mostly the coordination between networks for opportunities, and each area has an important tourist attraction that can be connected by a travel route. The main obstacle the readiness of each area to develop as a creative arts city. In the process of strengthening a network, it must have co-thought, co-creation and co-development, and must develop these three competencies. Knowledge, attitude, practice, and innovation arising from this research indicates that public information innovation or electronic database systems and social innovation should be policy promotion and strategy.